Balanced Scorecard as strategic management and performance in PT. Fajar Surya - Lukmansyah Rifai Amirudin; Rahmat Farulian (Jurnal Mantik, 2023)
This study aims to measure the company's performance and see the opportunities and challenges that exist outside the company in order to obtain alternative strategies to achieve company goals.  This research is qualitative research using an exploratory case study approach. Secondary data was obtained from internal companies during the period from 2015 to 2021.  The data collection method comes from the dashboard management application and the company's financial report overview. Researchers measure the performance of PT. Fajar Surya by looking at the actual achievements of the company's important indicators. The indicators used are the perspective of finance, customers, internal business processes, growth, and learning combined with the external side of the company through the TOWS analysis method. Data analysis used performance comparisons from each perspective during 2015-2021. This is an update (novelty) from previous studies that only used the BSC concept. The results of the research show that there are several strengths and weaknesses as well as opportunities and challenges that can be formulated to become alternative strategies. This research is expected to provide input regarding a comprehensive performance appraisal system for companies and additional empirical evidence regarding the concept of performance measurement with a combination of BSC and TOWS